BOB-RED queue management for IEEE 802.15.4 wireless sensor networks - Wu Jean-Lien (EURASIP Journal on Wireless Communications and Networking, 2011)
Abstract Multimedia services over resource constrained wireless sensor networks (WSNs) face a performance bottleneck issue from the gateway node to the sink node. Therefore, the queue management at the gateway node is crucial for diversified messages conveyed from the front nodes to the sink node. In this article, beacon order-based random early detection (BOB-RED) queue management is proposed. BOB-RED is a dynamic adaptation scheme based on adjusting beacon interval and superframe duration in the IEEE 802.15.4 MAC superframe accompanied with RED queue management scheme to increase the transmission efficiency of multimedia over WSNs. We focus on the performance improvement upon different traffic loads over WSNs. Evaluation metrics include end-to-end delay, packet delivery ratio, and energy consumption in IEEE 802.15.4 beacon enabled mode. Simulation results show that BOB-RED can effectively decrease end-to-end delay and energy consumption compared to the DropTail scheme.